2017
DOI: 10.1080/15299732.2017.1295420
|View full text |Cite
|
Sign up to set email alerts
|

Predicting a dissociative disorder from type of childhood maltreatment and abuser–abused relational tie

Abstract: We investigate the types of childhood maltreatment and abuser-abused relational ties that best predict a dissociative disorder (DD). Psychiatric inpatients (n = 116; mean age = 35; F:M = 1.28:1) completed measures of dissociation and trauma. Abuse type and abuser-abused relational ties were recorded in the Traumatic Experiences Questionnaire. Multidisciplinary team clinical diagnosis or administration of the SCID-D-R to high dissociators confirmed DD diagnoses. Logit models described the relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
(31 reference statements)
2
13
0
Order By: Relevance
“…Specifically in PNES, Ozcetin et al ( 59 ) found emotional abuse and emotional neglect to be significantly more frequent than in healthy controls. Kruger and Fletcher ( 69 ) showed that childhood emotional neglect by the biological parents and later emotional abuse by intimate partners predict the development of dissociative disorders. Importantly, emotional abuse has been associated with insular volume ( 70 ) and abnormal connectivity between the right TPJ and left insula ( 42 ) in FND patients.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically in PNES, Ozcetin et al ( 59 ) found emotional abuse and emotional neglect to be significantly more frequent than in healthy controls. Kruger and Fletcher ( 69 ) showed that childhood emotional neglect by the biological parents and later emotional abuse by intimate partners predict the development of dissociative disorders. Importantly, emotional abuse has been associated with insular volume ( 70 ) and abnormal connectivity between the right TPJ and left insula ( 42 ) in FND patients.…”
Section: Methodsmentioning
confidence: 99%
“…By using corroborating documentation from hospital, police, and child protection agencies or witnesses, several studies have confirmed histories of severe abuse in DID 29,34,35. In most clinical series, childhood abuse and/or neglect is reported by 90–100% of the patients directly during the study examination 36,37. Dissociative amnesia for childhood events may prevent such reports by some of the patients 38…”
Section: Developmental Traumatizationmentioning
confidence: 98%
“…29 , 34 , 35 In most clinical series, childhood abuse and/or neglect is reported by 90–100% of the patients directly during the study examination. 36 , 37 Dissociative amnesia for childhood events may prevent such reports by some of the patients. 38 …”
Section: Developmental Traumatizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Krüger and Fletcher (2017) in a well‐designed study of 116 women, via self‐reported questionnaire found that there is a strong correlation between emotional neglect (i.e. NO overt physical or sexual abuse) by biological parents with an involvement, later in life, in an overtly abusive relationship.…”
Section: Predisposing Factorsmentioning
confidence: 99%